Evaluation of Transaction Data Recording Program on Restaurant Tax Revenue in Banjar Regency Using CIPP Model - Nadia, Nadia; Udiansyah, Udiansyah; Hidayat, Yusuf (PT. Riset Press International, 2024)
The restaurant tax revenue in Banjar Regency consistently ranks among the top three contributors to local taxes. After assessing the potential and contribution of restaurant tax, considering the percentage of achievement in tax realization for taxpayers employing transaction data recording devices, and observing a tendency towards program stagnation, researchers find it crucial to evaluate the Transaction Data Recording Program's impact on restaurant tax revenue in Banjar Regency. This study aims to provide a descriptive overview of the implementation of the Transaction Data Recording Program on Restaurant Tax Revenue by the Regional Finance, Revenue, and Asset Management Agency of Banjar Regency. Utilizing a qualitative approach with a descriptive method, the analysis employs the CIPP evaluation model (Context, Input, Process, Product) for document analysis to gather data and information about the transaction data recording program in restaurant tax revenue. Data collection techniques involve observation, interviews, and documentation. The analysis and discussion of the research reveal that all aspects of the program components, including context, input, process, and product, have been executed well and meet expectations, yielding valuable results. Therefore, the decision regarding the program's sustainability is to continue its implementation.